The Relationship between the Study Habits and the Academic Performance of Medical Sciences Students - Hayede Rezaie Looyeh; Seyede Fateme Seyed Fazelpour; Shadman Reza Masoule; Minoo Mitra Chehrzad; Ehsan Kazem Nejad Leili (Journal of Holistic Nursing and Midwifery)
Abstract